The relationship between bumiputera's furniture entreprenuers' market orientation and their business performance: a case in Kelantan / Mazlina Mamat, Hadhifah Fadhlina Ismail and Tuan Mohd Rosli Tuan Hassan - Mamat, Mazlina; Ismail, Hadhifah Fadhlina; Tuan Hassan, Tuan Mohd Rosli (2010)
The demand scenario of furniture industry shows a significant growth. Malaysia's furniture export has recorded an 8.3% growth in 2010. Despite the promising market for Malaysian furniture in the global world, the contributions of Bumiputera furniture entrepreneurs are still small. From the observation, the Bumiputera furniture entrepreneurs give little attention on the implementation of market orientation which focused on three components: customer orientation, competitor orientation and inter-functional coordination. The furniture produced also failed to fulfill customer requirements. Therefore, this research is designed to assess the influence of market orientation on business performance of the Bumiputera furniture entrepreneurs. The data was successfully collected from 85 Bumiputera furniture entrepreneurs in Kelantan and then were analyzed through correlation and multiple regression to test the relationship and the strength of the association between variables. The findings show there are strong relationship between market orientation and business performance in which the implementation of market orientation will lead to a better performance. This research suggests for the business organization to succeed, market orientation has to be a vital part.